Understanding tourists’ intention in the face of earthquake risks: An analysis of word-of-mouth impact in the turkish tourism context - Yunus TOPSAKAL (Tourism and Hospitality Management)
Purpose – The objective of this research is to uncover the correlation between word-of-mouth communication, electronic word-of-mouth communication, perceived risk, and the intention to visit Turkey following an earthquake that occurred in February 2023. Methodology/Design/Approach – Data was collected from adult participants aged 18 and above in the United States of America. After data collection, any missing patterns in the data records were addressed, resulting in a refined dataset consisting of 501 participants. The analysis was performed using SmartPLS-4 and SPSS. Findings – According to the results, positive word-of-mouth about earthquakes does not decrease tourists’ perceived risk of visiting Turkey. However, positive word-of-mouth and electronic word-of-mouth about earthquakes do increase tourists’ intention to visit Turkey. Positive electronic word-of-mouth about earthquakes reduces tourists’ perceived risk of visiting Turkey. Lastly, the perceived risk associated with earthquakes decreases tourists’ intention to visit Turkey. Originality of the research – In a ground-breaking research endeavour that examines the seismic events of February 2023, this study pioneers an investigation into the complex motivations of tourists who choose to visit Turkey. It unravels the intricate interplay between word-of-mouth communication, electronic word-of-mouth, perceived risk, and the inclination to visit Turkey following the earthquake.